2023
DOI: 10.1177/03915603231155676
|View full text |Cite
|
Sign up to set email alerts
|

New insights about prognosis of Spermatic Cord Torsion

Abstract: Spermatic Cord Torsion (SCT) is a serious surgical emergency. Prospective studies regarding the prognosis of the torsed testis lack in the global literature. Prompt diagnosis and treatment are crucial to increase the risk of saving the torsed testis. Testicular salvage can be predicted by the duration of symptoms, along with the degree of twisting and the ultrasound findings, regarding the homogeneity of the testicular parenchyma. The “golden window” to salvage the testicular function is suggested to be at 4–8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For this, the duration of the symptoms, the degree of bending and the homogeneity of the testicular parenchyma together with advanced ultrasound findings are important. More than 4-8 hours after the onset of symptoms can lead to cell necrosis and, as a result, cell loss in the testicular tissue 4 . It has been stated in experimental studies that germ cells, particularly spermatogonia and spermatocytes, are most vulnerable type of cells to testicular ischemia 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, the duration of the symptoms, the degree of bending and the homogeneity of the testicular parenchyma together with advanced ultrasound findings are important. More than 4-8 hours after the onset of symptoms can lead to cell necrosis and, as a result, cell loss in the testicular tissue 4 . It has been stated in experimental studies that germ cells, particularly spermatogonia and spermatocytes, are most vulnerable type of cells to testicular ischemia 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated in experimental studies that germ cells, particularly spermatogonia and spermatocytes, are most vulnerable type of cells to testicular ischemia 5 . Additionally, it is said that in instances where early intervention is not made, the likelihood of conducting an orchiectomy rises 4 . It has been reported that using Testicular Torsion Risk Score will be appropriate to evaluate acute scrotal pain in early diagnosis.The parameters of this test are testicular swelling (2 points), hard testis (2 points), elevated testicles (1 point), absence of cremaster reflex (1 point), and nausea/vomiting (1 point) with a total score of 7 points 6 .…”
Section: Introductionmentioning
confidence: 99%